Reconfigurable Intelligent Surface-Aided Wireless Communications: Adaptive Beamforming and Experimental Validations - Muhammad Miftahul Amri (IEEE, 2021)
Recently, the fifth generation of cellular mobile communications (5G) network has been deployed and become pervasive. 5G offers a significant increase in terms of bandwidth and data rate compared to the previous generations. In addition, new technologies such as millimeter-wave (mmWave) technology and massive MIMO (mMIMO), have been proposed to meet the demand. However, some inevitable challenges still exist. In mmWave frequency, path loss and shadowing become more severe due to the radio electromagnetic (EM) wave characteristics. In this paper, we propose the utilization of reconfigurable intelligent surface (RIS) to aid wireless communications to overcome path loss and shadowing issues, by using a compressive sensing-based adaptive beamforming algorithm. To validate the theory, hypothesis, and simulation results, we have designed, fabricated, and conducted experiments with a 1-bit RIS testbed. The results show that the bit error rate (BER) and signal-to-noise ratio (SNR) of the received signal are significantly improved when the proposed RIS is employed. Further, we have also demonstrated a video streaming application aided by the proposed RIS as one of the potential RIS deployment scenarios.